IT GOVERNANCE: A STRATEGIC ALIGNMENT FOR INFORMATION TECHNOLOGY/BUSINESS - Henderi Henderi; Yeni Nuraeni; Junaidi Junaidi; Rahmad Hidayat (CCIT Journal, 2010)
Information technology (IT) is a critical asset for effectiveness organizational governance. Therefore, the organization’s and IT’s and business’s expertise need a good IT governance. IT governance as a tool for aligning IT with business, is required to explain the new role of IT organizations, measuring the contribution of each organization’s components, helping identify the impact and benefits of IT investment which has been done, decision making, and make a better project. Conversely, the IT governance which ineffective can lead to losses of business, impairment of reputation, weaken the ability of competitiveness, lack of precision project, inefficient, quality of production is not in line with expectations, and inability to fulfill the innovation and benefits that were promised. Meanwhile, strategic alignment (in the IT business) which can either creating new opportunities and increased competitive advantage for companies well. Thus, it is necessary to create strategic alignment IT-business and ensure IT governance goes according to planned. This article intends to discusse and provide information about strategic IT-business alignment as one component of good IT governance. Once understood, the directors and CEO can identify opportunities and develop a good strategic alignment to increase IT business alignment in order to ensure companies continuity.